ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL BERBASIS PjBL TERINTEGRASI KEARIFAN BUDAYA LOKAL TERNATE - Fitriana Eka Chandra; Ahmad Afandi (STKIP Andi Matappa, 2021)
This study aims to analyze the need to develop teaching materials used in the Mathematics-Economics course. This study uses a qualitative descriptive method oriented to the development of a product. The data collection instrument used observation and interview guidelines. Data analysis in this study used the Miles-Huberman Interactive Analysis, which consisted of data reduction, data presentation, and conclusion drawing. Based on the analysis, it is known that students have not been able to understand concepts that can be used to solve real problems in everyday life, learning the application of functions in economic activities is still theoretical, the learning carried out is also still teacher-oriented, students cannot be trained independently in learning. The material chosen is the application of functions integrated into the wisdom of the Local Cultural Wisdom of the Barito Market Traders so that students are better known. The tasks given in the form of projects are in accordance with the PjBL learning syntax. Based on these reasons, it is necessary to develop teaching materials in the form of an E-Module for economic mathematics courses based on PjBL and integrated with Local Cultural Wisdom, Barito Market Traders, Ternate City, to make learning active for students and more applicable.